Development of a dual output switch mode power converter (SMPS) for audio/video application - Sein, Thiri Win. (2013)
A switch mode power supply (SMPS) is an electronic power supply unit that incorporates power transistors that are continuously switching on and off with high frequency in order to provide the transfer of electric energy. An output parameter is controlled by varying duty cycle, frequency or a phase shift of these transitions while a linear maintains the desired output voltage with dissipating excess power. In this report, a switch mode power supply is designed and implemented with the requirement of dual output with total power of 250W for audio and video application.